Ziggy was here: Tom Wilson's newspaper comic, World War II, and the role of graffiti in sequential art. Issue 1 (2nd January 2022) - Abate, Michelle Ann
ABSTRACT: This essay offers a new perspective on the creative origins, aesthetic qualities, and socio-cultural significance of Tom Wilson's newspaper comic, Ziggy . More specifically, I point out the ways in which Tom Wilson's well-known character from the closing decades of twentieth century contains elements of visual, thematic, and cultural overlap with an equally well-known figure from the middle portion of the century: Kilroy. Placing Ziggy in dialogue with Kilroy brings together two iconic figures from the history of American cartooning, inviting us to reconsider them both. While much has been written about the important role that the Second World War played in U.S. comics, these discussions have largely focused on the influence of comic books. The suggestive echoes between Ziggy and Kilroy call attention to the role that individual characters who circulated outside of the floppies played in the rise of sequential art during this era. More specifically, given that the figure of Kilroy was scrawled on walls, tanks, and barracks, it highlights the important but long overlooked role of modern graffiti in contemporary comics.